Gear Tooth Failure Detection by the Resonance Demodulation Technique and the Instantaneous Power Spectrum Method – A Comparative Study - Ahmad Ghasemloonia; Siamak Esmaeel Zadeh Khadem (Shock and Vibration)
The role of gears in industry for speed and torque variation purposes is obvious. The gearbox diagnostic methods have been improved quickly in recent years. In this paper, two of the newest methods, the resonance demodulation technique (R.D), and the instantaneous power spectrum technique (IPS) are applied to gearbox vibration signals and their capabilities in fault detection are compared. Yet, the important role of time averaging should not be dispensed with, as it is the primary step for both techniques. In the present study, the mathematical method of these techniques, according to the mathematical vibration model of gears, is introduced, these techniques are applied to the test rig data, and finally the results of both methods are compared. The results indicate that in each method, the location of fault can be estimated and it is located in the same angular position in both methods. The IPS method is applicable to severe faults, whereas the resonance demodulation technique is a simple tool to recognize the fault at each severity and at the early stages of fault generation.